Lysosomal degradation and sorting of apolipoprotein E in macrophages. - J Deng; V Rudick; L Dory (Journal of Lipid Research, 1996)
We previously reported that a substantial amount of newly synthesized apoE in mouse macrophages is degraded prior to secretion; a portion of this pool of apoE can be rescued by the addition of HDL3 to the incubation medium. In the present studies, the location and nature of the intracellular degradation of apoE were more closely examined. Inhibitors of protein trafficking (brefeldin A) as well as a number of protease inhibitors were used. The experiments using brefeldin A (5 micrograms/ml) clearly established that neither the endoplasmic reticulum nor the Golgi complex are the sites of apoE degradation. Using a pulse-chase design, [35S]apoE cannot be chased out in the presence of brefeldin A and remains undegraded within the cell. The accumulated apoE lacks the sialic acid residues, indicating that this final stage of processing must occur in the trans-Golgi network or later. Lysosomotropic agents, ammonium chloride and chloroquine, on the other hand, inhibit apoE degradation by over 70 and 80%, respectively, while total cell protein degradation remains unaffected. Similarly, a cocktail consisting of four lysosomal protease inhibitors (pepstatin, E-64, chymostatin, and antipain), inhibits specifically apoE degradation by over 60%. In contrast, ALLN, an inhibitor of Ca(2+)-dependent cysteine proteases, has a moderate effect on apoE degradation (30% inhibition) and a more pronounced effect on total protein degradation. These data suggest that the site of intracellular apoE degradation in the macrophage is the lysosome. These conclusions are supported by light and electron microscopy of macrophages, clearly showing the presence of immunoreactive apoE (along with cathepsin D) in the endosomal/lysosomal compartment of control and lysosomotropic agent-treated cells. In contrast, little or no labeling is seen in this compartment in brefeldin A-treated cells. At lower concentrations of the lysosomotropic agents, the extent of inhibition of apoE degradation is compensated for by its increased secretion, in a manner analogous to the effect of these agents on lysosomal enzymes. Higher concentrations of these agents, which lead to a profound inhibition of apoE degradation, also specifically block apoE secretion. The block in apoE secretion in the presence of high concentrations of chloroquine leads to undiminished or higher concentrations of immunoreactive apoE in the endosomal/lysosomal compartment, suggesting that apoE is targeted for lysosomal degradation directly, without prior secretion or surface association. These data strongly suggest pH-dependent sorting of apoE in macrophages to the degradative and secretory pathways and imply a protein-protein interaction in the process.